Media Exposure and Post-traumatic Stress Symptoms in the Wake of the November 2015 Paris Terrorist Attacks: A Population-Based Study in France - Robert, Maëlle; Stene, Lise Eilin; Garfin, Dana Rose; Vandentorren, Stéphanie; Motreff, Yvon; du Roscoat, Enguerrand; Pirard, Philippe (Frontiers in Psychiatry, 2021)
The intense mass media coverage of the Paris terrorist attacks on 13 November 2015 exposed a substantial majority of the French population to the attacks. Prior research has documented the association between media exposure to terrorism and posttraumatic stress symptoms (PTSS). The present study replicated and extended these findings in a French sample. A population-based sample (N=1,760) was drawn from a national web-enabled panel in June 2016. Hours of attack-related media exposure (i.e., TV-watching, viewing internet images, engaging in social media exchanges) in the three days following the attacks were assessed. Multivariate regression models, adjusting for gender, age, direct exposure (i.e., witnessing in person or knowing someone injured or killed), residential area, social support, pre-attack mental health services utilization and other adverse life events, examined the association between media exposure and PTSS (assessed using the self-report PCL-5 tool). Compared to those who reported less than 2 hours of attack-related television exposure, those reporting 2-4 hours (β=3.1, 95% CI= 0.8-5.3) or greater than 4 hours (β=4.7, 95% CI= 2.0-7.4) of media exposure reported higher attack-related PTSS. This finding was replicated with social media use: those with moderate (β=3.2, 95% CI=0.9-5.5) or high (β=6.8, 95% CI=1.9-11.7) use reported higher PTSS than those reporting none. Subanalyses demonstrated that media exposure and PTSS were not associated for those directly exposed to the attacks. Results highlight the potential public health risk of extensive mass media exposure to traumatic events.